The growth and prospects for the oil palm plantation industry in Indonesia - Varkkey, H. (Malaysian Palm Oil Board, 2012)
This article provides a historical political economy perspective of the Indonesian oil palm plantation sector. It aims to shed light on the process of how Indonesia took over from Malaysia in becoming the world’s current largest producer of palm oil. This article argues that the regional trend of state-led development that relied on agribusiness as a major sector played a major role in the development of oil palm as an important crop in the region, especially in Malaysia and Indonesia. Indonesia specifically promoted and encouraged the expansion of oil palm as a way to fulfill state developmental aims; identifying it as a lucrative source of revenue, foreign exchange, and rural employment. With oil palm playing such an important role in the Indonesian economy, the state has outlined plans for rapid area expansion, to maintain its world dominance in the sector. Malaysian and Singaporean companies are currently major players in the Indonesian oil palm plantation sector, and continue to reap the benefits of this lucrative crop alongside local firms.